Television as a Hybrid Repertoire of Memory - Hagedoorn, Berber (VIEW Journal of European Television History and Culture, 2013)
In this article, television is reconsidered as a hybrid ‘repertoire’ ofmemory. It is demonstrated how new dynamic production and scheduling practicesin connection with highly accessible and participatory forms of user engagementoffer opportunities for television users to engage with the past, and how suchpractices affect television as a practice of memory. The media platform HollandDoc is discussed as a principal casestudy. By adopting and expanding Aleida Assmann’s model of the dynamics ofcultural memory between remembering and forgetting, a new model to studytelevision as cultural memory is proposed which represents the medium’shybridity in the multi-platform era.